Stratigraphic evolution and drowning steps of a submerged isolated carbonate platform in the northern South China Sea - Chen, Wanli; Wu, Shiguo; Wang, Dawei; Betzler, Christian; Ma, Yongsheng (Frontiers in Marine Science, 2023)
Drowned carbonate platforms on passive margins present a paradox, because their great growth potential exceeds the typical rates of passive margin subsidence and any relative sea-level rise driven by long-term processes in the geologic record. In this study, manned submersible observations, sampling, and high-resolution acoustic data were used to investigate a drowned isolated carbonate platform cropping out at a water depth of 536–800 m in the northern South China Sea. Based on the results, the Early Miocene strata of the platform are grouped into three units (AU1, AU2, and AU3) that formed on the fault-created topography. The fault-created topography served as a template for the onset of the carbonate platform deposition and as a pedestal for the localization of backstepped platforms in response to accommodation space variations, primarily driven by rapid subsidence and eustatic rises during the Early Miocene. The Middle Miocene strata of the platform are grouped into four units (AU4, PU1, PU2, and PU3), exhibiting a general switch from dominantly aggrading to dominantly prograding platform margins, in tandem with the cessation of faulting. The biostratigraphy and established seismic–stratigraphic correlations indicate that the carbonate platform was submerged during the late Middle Miocene. The banktop consists of a heterozoan carbonate factory dominated by large benthic foraminifera and coralline algae. This facies was deposited during a time interval when summer monsoon-induced upwelling triggered heterozoan factory turnover in other carbonate platforms in the region, such as at well XK-1 (Xuande Platform). The asymmetric backstepping of the platform margins demonstrates that summer monsoon-driven currents influenced the platform drowning. Therefore, summer monsoon-induced upwelling was a major factor influencing platform drowning during the late Middle Miocene. Platform growth did not persist due to the high subsidence rate throughout the Late Miocene. This study provides new insights into the drowning mechanism of a Miocene carbonate platform in the northern South China Sea and a new seismic analog for other ancient, isolated platforms worldwide.